Compensation of inhomogeneous fluorescence signal distribution in 2D images acquired by confocal microscopy - Michálek, Jan; Capek, Martin; Kubínová, Lucie (Microscopy research and technique, 2011)
In images acquired by confocal laser scanning microscopy (CLSM), regions corresponding to the same concentration of fluorophores in the specimen should be mapped to the same grayscale levels. However, in practice, due to multiple distortion effects, CLSM images of even homogeneous specimen regions suffer from irregular brightness variations, e.g., darkening of image edges and lightening of the center. The effects are yet more pronounced in images of real biological specimens. A spatially varying grayscale map complicates image postprocessing, e.g., in alignment of overlapping regions of two images and in 3D reconstructions, since measures of similarity usually assume a spatially independent grayscale map. We present a fast correction method based on estimating a spatially variable illumination gain, and multiplying acquired CLSM images by the inverse of the estimated gain. The method does not require any special calibration of reference images since the gain estimate is extracted from the CLSM image being corrected itself. The proposed approach exploits two types of morphological filters: the median filter and the upper Lipschitz cover. The presented correction method, tested on images of both artificial (homogeneous fluorescent layer) and real biological specimens, namely sections of a rat embryo and a rat brain, proved to be very fast and yielded a significant visual improvement.
Keywords: algoritmy; krysa rodu Rattus; Animals; Image Processing, Computer-Assisted; zvířata; Microscopy, Confocal; konfokální mikroskopie; počítačové zpracování obrazu; Brain; Rats; mozek; Algorithms